Episodic post‐rift deformation in the south‐eastern Australian passive margin: evidence from the Lapstone Structural Complex. Issue 11 (21st February 2014) - McPherson, Andrew; Clark, Dan; Macphail, Mike; Cupper, Matthew
ABSTRACT Identifying the influence of neotectonics on the morphology of elevated passive margins is complicated in that major morpho‐structural patterns might plausibly be explained by processes related to late Mesozoic to early Cenozoic rifting and/or differential erosion induced by Cenozoic epeirogenic uplift. The proportional contribution of each process can vary from continent to continent, and potentially even within the same passive margin. In the passive margin setting of the southeast Australian highlands the documented occurrence of neotectonic deformation is rare, and accordingly its role in landscape evolution is difficult to establish. The results of investigations within the Lapstone Structural Complex, which forms the eastern range front of the Blue Mountains Plateau, provide evidence for two periods of Cenozoic neotectonic uplift in this part of the highlands. The first, demonstrated by seismic and structural evidence, is suggested to have occurred in the Paleogene, and is thus unrelated to Cretaceous rifting. The second period, demonstrated by evidence from the Kurrajong Fault (presented herein) suggests that uplift occurred in both the Mio‐Pliocene and the Middle Pleistocene. The cumulative Neogene and younger uplift of 15 m determined for the Kurrajong Fault is less than 10% of the 130 m of total measured throw across the fault. The apparently minor contribution of neotectonism to the current elevation of the Blue Mountains Plateau supports a predominantly erosional exhumation origin for the topographic relief at the plateau's eastern edge. This finding contrasts with evidence from fault complexes associated with similar topographic relief elsewhere in the south‐eastern highlands, indicating that present‐day topography cannot be directly related to relief generated by Neogene and younger uplift, even from relatively closely‐spaced (< 150 km) structures within the same passive margin. These findings have implications for understanding the spatio‐temporal variability of post‐rift faulting in continental passive margin settings and the evolution of landscapes therein. © Commonwealth of Australia. Earth Surface Processes and Landforms © 2014 John Wiley & Sons, Ltd.